Assessment of Dairy Cattle Management Practices Followed by Cooperative Dairy Farmers in North-Eastern Hilly State, Tripura - Deb, Debapritam; Kalita, Girin; Paul, Abhishek; Goswami, Ranjana; Buragohain, Rajat; Das, Hemen (International Journal of Bio-resource and Stress Management, 2026)
A comprehensive field study was conducted from August, 2023 to January, 2024 in Tripura, India to understand dairy management practices among cooperative members. Three districts were selected, and a total of 120 respondents were randomly sampled. Based on herd size, the respondents were categorized into three groups: small (< 3 animals), medium (3–8 animals), and large herd (> 8 animals). Using a structured interview schedule, data were gathered on feeding, breeding, housing, milking, calf care, along with reproductive and healthcare management practices. Results showed that dairy cattle were reared semi-intensively, were fed an average daily ration of 5.92±0.39 kg green fodder, 1.85±0.07 kg concentrate, and 7.34±0.27 kg dry fodder per animal. Bran was the predominant concentrate ingredient. Artificial insemination was the primary breeding method (85.83%). In terms of housing, most farmers used concrete flooring (64.17%) and employed a tie-barn system (76.67%), with corrugated galvanized iron (GI) sheet roofing. The average floor space per animal was 19.37±0.52 sq ft while the overall roof height was 9.38±0.19 ft.The manual “knuckling” milking method was used by the majority (64.17%) of farmers. Most farmers (87.5%) dried off pregnant animals two months before parturition and administered colostrum within two hours of birth. Calf deworming was nearly universal (97.5%), though no dehorning was practiced. Repeat breeding and anestrous were the most common reproductive problems. While deworming was widespread, routine vaccination was lacking. In case of illness, Majority of farmers (83.33%) sought treatment from private practitioners.